Redes de interações de frugivoria de sabiás (turdidae) em dois estágios sucessionais na Mata Atlântica no Sul do Brasil - Malmoria, Pamela Eliana (2021)
Birds are among the most important seed dispersers, potentially depositing seeds away from their mother plants, increasing the likelihood of survival and the establishment of new individuals. The functional attributes of birds determine, among other aspects, their ability to explore different types of resources in the forest environment. However, the selection of resources by birds also varies depending on the structure and dynamics of plant communities, especially in fragmented environments that make up mosaics of fragments at different sucessionais stages. In this work, we evaluated the mutualistic networks between frugivorous birds and plants, and the variation of morphological attributes of birds with potential influence on fruit selection. We used as a study system birds belonging to the Turdidae family, Turdus albicollis, T. amaurochalinus, T. flavipes, T. rufiventris and T. subalaris. The work was carried out in six fragments of Mixed Ombrophilous Forest in initial (3) and advanced (3) successional stages in the Pro-Mata Natural Heritage Reserve, Rio Grande do Sul, Brazil. Birds were captured with mist nets and their diet was estimated by analyzing the seeds released in the feces at the time of capture. The attributes measured for the birds were: width, length and height of the beak, length of the tarsus and tail, weight and Kipp index. Considering the average values of the morphological measures for the five sampled species (n = 146 individuals), we did not find significant differences between successional stages. Considering the intraspecific variation, there was a difference between stages in T. flavipes for the length of the beak (F = 2.88, p <0.05) and for T. rufiventris in the weight and length of the tarsus (F = 3.17, p <0.05, F = 3.04, p <0.05 respectively). In this study, the species Myrsine lorentziana (Fam. Primulaceae) was registered more frequently, interacting through bird feces. We observed, in the initial stage, individuals of T. albicollis and T. rufiventris consuming the same fruits; while, in the advanced stage, there is a difference in the size of fruit consumed by these two species. There is a partition of trophic niches among the species of the Turdidae family, showing a difference in the size of the fruits consumed depending on the successional stage. The studied Turdus species at Pro-Mata Natural Heritage Reserve contribute substantially to seed dispersal processes in fragmented areas. However, our study shows that, despite being generalist species, the studied Turdus species, showed differences in relation to the resources consumed according to the successional stage, partly accompanied by variations in morphology, which may be related to the reduction of competition. intraspecific.